Negative electrode material, preparation method thereof and battery

By using a biomass-based hard carbon material and forming a carbon cladding layer on its surface, the problem of insufficient performance of the existing sodium ion battery negative electrode material is solved, and a negative electrode material with high capacity, excellent kinetics and good cycle performance is achieved.

CN119581509AActive Publication Date: 2025-03-07JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411514708.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The negative electrode material performance of existing sodium ion batteries is insufficient, which limits its application in the field of large-scale energy storage.

Method used

A biomass-based hard carbon material is used as the matrix of the negative electrode material, and a carbon cladding layer is formed on its surface. By controlling the atomic ratio of C and O elements and the thickness of the carbon cladding layer, the capacity and dynamic performance of the material are improved.

Benefits of technology

The charge and discharge specific capacity, first effect and cycling performance of the negative electrode material are improved, and the rapid transmission of sodium ions and structural stability of the material are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581509A_ABST
    Figure CN119581509A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative electrode material, a preparation method thereof and a battery. The negative electrode material comprises a substrate and a carbon coating layer coating at least part of the surface of the substrate, wherein the matrix comprises hard carbon, the hard carbon is a biomass-based hard carbon material, the hard carbon contains a C element and an O element, and the atomic ratio of O to C is (1: 20)-(1: 10). The preparation method of the negative electrode material comprises the following steps: soaking a pretreated biomass material in a chloride solution, and sintering to obtain a hard carbon precursor; the preparation method comprises the following steps: mixing a hard carbon precursor with an acidic solution, adding peroxydisulfate, mixing, separating and drying to obtain a hard carbon material containing an epoxy group; and carrying out carbon coating treatment on the hard carbon material containing the epoxy group, and forming a carbon coating layer on at least part of the surface of the hard carbon to obtain the negative electrode material. The capacity and the dynamic performance of the negative electrode material can be improved, and the capacity, the first efficiency and the cycle performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode material and a preparation method thereof, and a battery. Background Art

[0002] With the proposal of the dual carbon goals and the vigorous development of new energy electric vehicles and clean energy, the energy storage field has broad development prospects. Although lithium-ion batteries have been widely used, their further application in the field of large-scale energy storage is limited due to factors such as the limited lithium resources, uneven geographical distribution and high costs. Sodium and lithium belong to the same main group elements. They not only have similar physical and chemical properties and energy storage mechanisms, but also sodium resources have the advantages of high earth abundance, low extraction technology difficulty and low cost. Therefore, sodium-ion batteries have very broad application prospects in the field of large-scale energy storage.

[0003] Carbon-based materials are the most developed negative electrode materials for sodium-ion batteries. Carbon-based materials have received more attention due to their advantages such as wide resources, stable structure and low preparation cost. Graphite negative electrode materials have been successfully applied in lithium-ion batteries, but because sodium ions are difficult to embed into them, the application of graphite in sodium-ion batteries is limited. Therefore, the development of high-capacity sodium ion negative electrode materials is the key to promoting sodium-ion battery technology.

[0004] Therefore, the negative electrode materials used for sodium ion batteries in the prior art still need to be improved and developed. Summary of the invention

[0005] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a negative electrode material and a preparation method thereof and a battery, which are conducive to improving the capacity and kinetic performance of the negative electrode material, facilitating the rapid transmission of sodium ions, and further facilitating improving the capacity, first efficiency and cycle performance of the battery.

[0006] In order to solve the above technical problems, this application is implemented as follows:

[0007] According to one aspect of the present application, an embodiment of the present application provides a negative electrode material, the negative electrode material comprising a substrate and a carbon coating layer coated on at least a portion of the surface of the substrate;

[0008] Wherein, the matrix includes hard carbon, the hard carbon is a biomass-based hard carbon material, and the hard carbon contains C element and O element, and the atomic ratio of O and C satisfies:

[0009] O:C=1:20~1:10.

[0010] In addition, the negative electrode material according to the present application may also have the following additional technical features:

[0011] In some embodiments, the atomic ratio of O and C satisfies:

[0012] O:C=1:20~1:15.

[0013] In some of the embodiments, the hard carbon has a fibrous corrugated structure.

[0014] In some embodiments, the carbon coating layer has a thickness of 5 nm to 10 nm.

[0015] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a negative electrode material, which comprises the following steps:

[0016] The pretreated biomass material is soaked in a chloride solution and sintered to obtain a hard carbon precursor;

[0017] The hard carbon precursor is mixed with an acidic solution, and then peroxodisulfate is added, and after mixing, separation and drying, a hard carbon material containing epoxy groups is obtained;

[0018] The hard carbon material containing epoxy groups is subjected to carbon coating treatment to form a carbon coating layer on at least a portion of the surface of the hard carbon to obtain a negative electrode material.

[0019] In some embodiments, the preparation of the pretreated biomass material includes: sequentially alkali washing, water washing, acid washing, water washing and drying the biomass material to obtain the pretreated biomass material.

[0020] In some embodiments, the concentration of the alkaline solution used in the alkaline washing is 0.5-1 mol / L.

[0021] In some embodiments, the concentration of the acid solution used in the pickling is 0.5-1 mol / L.

[0022] In some of the embodiments, during the alkaline washing, acid washing or water washing process, the solid-liquid ratio of the biomass to the solution is 1:50 to 1:200 g / mL.

[0023] In some embodiments, the drying temperature is 70° C. to 100° C., and the drying time is 10 h to 16 h.

[0024] In some of the embodiments, the biomass material has a fibrous structure.

[0025] In some embodiments, the biomass material includes at least one of cellulose, bamboo, coconut shell, macadamia shell, walnut shell, pine nut shell, peanut shell, rice straw, cotton stalk skin, bagasse, reed, reed bamboo, straw, walnut shell, coconut skin or lignin.

[0026] In some embodiments, the step of obtaining a hard carbon precursor satisfies at least one of the following features (1) to (5): (1) the chloride solution includes at least one of a sodium chloride solution, a potassium chloride solution or a chromium chloride solution; (2) the concentration of the chloride solution is 0.05 to 0.5 mol / L; (3) the solid-liquid ratio of the pretreated biomass material during immersion in the chloride solution is 10:1 to 20:1 g / L; (4) the sintering is carried out under an inert gas atmosphere, and the flow rate of the inert gas is 40 to 80 mL / min; the heating rate of the sintering is 1 to 5°C / min, the sintering temperature is 500 to 1000°C, and the time is 2h to 5h; (5) the particle size D50 of the hard carbon precursor is 5μm to 10μm.

[0027] In some embodiments, the step of obtaining a hard carbon material containing epoxy groups satisfies at least one of the following characteristics (1) to (4): (1) the ratio of the hard carbon precursor, the acidic solution and the peroxodisulfate is 100:10000:1 to 100:5000:2 in terms of g:mL:M; (2) the acidic solution comprises concentrated sulfuric acid with a mass fraction of not less than 98%; (3) the peroxodisulfate comprises at least one of potassium peroxodisulfate, nickel peroxodisulfate or cobalt peroxodisulfate; (4) the drying temperature is 70°C to 100°C.

[0028] In some embodiments, the carbon coating layer includes pyrolytic carbon formed by thermal decomposition of resin or high molecular polymer.

[0029] In some embodiments, the mass ratio of the resin or high molecular polymer to the hard carbon material containing epoxy groups is 5:1 to 10:1.

[0030] In some embodiments, the resin or polymer includes at least one of phenolic resin, epoxy resin, acrylic resin, furfural resin, polyethylene glycol, polyethylene oxide, polyethylene or polypropylene.

[0031] In some embodiments, the carbon coating process is a calcination process performed in an inert gas atmosphere.

[0032] In some embodiments, the heating rate of the carbon coating treatment is 1-20° C. / min, the temperature of the carbon coating treatment is 500-700° C., and the time is 1 h to 8 h.

[0033] In some embodiments, the carbon coating layer has a thickness of 5 nm to 10 nm.

[0034] According to another aspect of the present application, an embodiment of the present application provides a battery, wherein the battery includes a negative electrode sheet, and the negative electrode sheet includes the negative electrode material as described above, or the negative electrode material prepared by the above method.

[0035] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0036] In an embodiment of the present application, the negative electrode material provided includes a substrate and a carbon coating layer, wherein the substrate adopts a biomass-based hard carbon material, and the hard carbon contains carbon (C) elements and oxygen (O) elements, and the atomic ratio of the C element and the O element is defined. Thus, by making the hard carbon contain O elements, and making the ratio of the O element and the C element within the defined range, the negative electrode material can be made to exhibit higher capacity and faster dynamics, and the interlayer spacing can be expanded, which is conducive to achieving the rapid transmission of sodium ions, and is conducive to improving the charge and discharge specific capacity, first effect and cycle performance of the negative electrode material. At the same time, a carbon coating layer is arranged on the surface of the substrate, and the carbon coating layer can be used to reduce the specific surface area, increase the mechanical strength and conductivity of the active material (negative electrode material), effectively slow down the structural degradation of the negative electrode material during repeated sodiumization / de-sodiumization, and improve the structural stability of the negative electrode material.

[0037] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Shown is a scanning electron microscope image (SEM image) of the biomass material provided in Example 1 of the present invention.

[0039] Figure 2 Shown is a scanning electron microscope image (SEM image) of the negative electrode material provided in Example 1 of the present invention.

[0040] Figure 3 Shown is a transmission electron microscope image (TEM image) of the negative electrode material provided in Example 1 of the present invention.

[0041] Figure 4 Shown are XRD patterns of the negative electrode materials provided by Example 1 (epoxy group-rich carbon material) of the present invention and Comparative Example 1 (original carbon material).

[0042] Figure 5 Shown is the EDS image of the negative electrode material provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0043] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0044] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0045] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0046] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0047] Among the negative electrode materials of sodium ion batteries, although graphite materials are widely used, they also have the disadvantage that sodium ions are difficult to embed into them. In order to alleviate this disadvantage, it is necessary to develop negative electrode materials with high capacity of sodium ions. Among them, hard carbon is considered to be a very promising negative electrode material for sodium ion batteries because of its advantages such as large interlayer spacing, good structural stability and low cost. However, existing hard carbon materials, such as some biomass-based hard carbon materials, have disadvantages such as low capacity and low first efficiency, which limits their further development in the field of negative electrodes of sodium ion batteries. Therefore, it is necessary to modify the hard carbon materials to improve their electrochemical properties and improve their application effect in the negative electrode of sodium ion batteries.

[0048] The inventors of this application have found that hard carbon materials, due to their unique microstructure, can effectively insert and remove sodium ions, and are increasingly attracting the attention of researchers. Biomass materials are one of the good hard carbon precursor materials, and some biomass-derived hard carbon materials have a unique nanofiber structure, which can effectively shorten the ion / electron transmission path and improve the conductivity of the material. In addition, the disordered arrangement of pseudo-graphene nanocrystals distorted at the microscopic level in hard carbon materials has a larger interlayer distance than graphite, and this structure reduces the energy barrier during sodium dissociation. Studies have shown that closed nanopores and carbon layers with appropriate spacing can accommodate sodium ions and have a high reversible capacity. However, this capacity is limited to lower current densities and performs poorly at higher current densities, which is attributed to the poor sodium storage kinetics of hard carbon materials. At the same time, biomass hard carbon has a large specific surface area, low initial coulomb efficiency (ICE), and poor cycle performance, which hinders the practical application of hard carbon.

[0049] Therefore, the inventors of this application have fully considered the characteristics of hard carbon materials, and improved the capacity, first efficiency, cycle performance and other properties of the materials by modification, coating, etc., so as to effectively alleviate the above problems. In view of this, this application provides a negative electrode material, a method for preparing a negative electrode material and a battery, and the application is described in detail below.

[0050] [Anode material]

[0051] In some embodiments, the present application provides a negative electrode material, which includes a substrate and a carbon coating layer coated on at least a portion of the surface of the substrate;

[0052] The matrix includes hard carbon, which is a biomass-based hard carbon material. The hard carbon contains C and O elements, and the atomic ratio of O to C satisfies:

[0053] O:C=1:20~1:10.

[0054] It should be noted that in the present application, the "coating" is not limited to direct coating, but also includes indirect coating. For example, the carbon coating layer coats the substrate, and there may be no other structure between the carbon coating layer and the outer surface of the substrate, or there may be one or more layers of other structures between the carbon coating layer and the outer surface of the substrate. Preferably, there is no other structure between the carbon coating layer and the outer surface of the substrate.

[0055] In the present application, the carbon coating layer is formed or coated on at least part of the surface of the substrate, which can protect or improve the substrate, and can be used to improve the structural stability of the negative electrode material, improve the first coulombic efficiency of the negative electrode material, and reduce the specific surface area of ​​the negative electrode material. The carbon coating layer is coated or formed on at least part of the surface of the substrate, which means that the carbon coating layer can completely encapsulate the substrate in the carbon coating layer, or the carbon coating layer can only coat a part of the outer surface of the substrate; that is, the carbon coating layer can completely coat the substrate, or can coat part of the surface of the substrate, preferably completely coat it.

[0056] The negative electrode material provided is a core-shell structure, wherein the core is made of hard carbon, and the outer shell or shell layer includes a carbon coating layer (carbon material layer). Among them, the hard carbon is used as the core, and it is particularly prominent that the hard carbon in the present application is a biomass-based hard carbon material, that is, the precursor of the hard carbon can be made of biomass, which is a biomass-derived hard carbon material, and the hard carbon contains C elements and O elements, such as, Figure 5 It is shown that the negative electrode material provided by the embodiment of the present invention contains C element and O element, and the atomic ratio of O and C is limited to satisfy: O:C=1:20~1:10. Therefore, by making the hard carbon contain C element and O element, and making the ratio of O element and C element within the limited range, it has a greater contribution to effectively improving the sodium ion adsorption capacity of the material. At the same time, the hard carbon containing oxygen element can effectively reduce the free volume of sodium ion migration, which is beneficial to improving the kinetics of the material. That is, by making the hard carbon contain O element, and making the ratio of O element and C element within the limited range, the negative electrode material can show higher capacity and faster kinetics, and the interlayer spacing can be appropriately expanded during the sodiumation / de-sodiumation process, which is beneficial to achieve rapid transmission of sodium ions and improve the charge and discharge specific capacity, first efficiency and cycle performance of the negative electrode material.

[0057] At the same time, a carbon coating layer is provided on the surface of the substrate, which can be used to reduce the specific surface area, increase the mechanical strength and conductivity of the active material (negative electrode material), effectively slow down the structural degradation of the negative electrode material during repeated sodiumization / desodiumization, improve the structural stability of the negative electrode material, and improve the first coulombic efficiency of the negative electrode material.

[0058] Moreover, the above-mentioned hard carbon is a biomass-based hard carbon material. The hard carbon material is prepared using biomass as a precursor. It has a wide source and is inexpensive. It is a low-cost, large-scale, practical industrial production solution for the negative electrode material of sodium-ion batteries. In addition, from the perspective of green and recyclability, the strategy of using biomass to synthesize electrode materials is of great significance, and biomass-derived carbon exhibits good electrochemical properties.

[0059] Optionally, the base hard carbon or the negative electrode material has a fiber structure.

[0060] In some preferred embodiments of the present application, the prepared negative electrode material or hard carbon has a fibrous structure, shortens the ion transfer path, improves the electrochemical reaction kinetics, effectively reduces the specific surface area of ​​the material, and has sufficient reaction active sites. At the same time, it also has a high gram capacity, making the negative electrode material a potential high-capacity sodium ion battery negative electrode material.

[0061] As an example, the atomic ratio of O and C may be any one of 1:20, 1:19, 1:18, 1:17, 1:16, 1:15, 1:14, 1:13, 1:12, 1:11, 1:10 or a range between any two of them.

[0062] By making the atomic ratio of O and C within the above range, it is helpful to make the content of oxygen-containing groups or compounds in the hard carbon within an appropriate range, which helps to improve the contribution of the material to the sodium ion adsorption capacity and the kinetics of the negative electrode material, so that the oxygen-rich hard carbon material exhibits higher capacity and faster kinetics. In the sodium / de-sodiumization process, the strong attraction of oxygen-containing compounds is used to appropriately expand the interlayer spacing, which is conducive to the rapid transmission of sodium ions. If the atomic ratio of O and C is too small (close to zero), the content of oxygen in the hard carbon is reduced, and it cannot effectively play a beneficial role in improving the contribution of the material to the sodium ion adsorption capacity and the kinetics of the negative electrode material; if the atomic ratio of O and C is too large, the oxygen content is too much, resulting in a lower first efficiency during the first cycle of charge and discharge, affecting the cycle life of the battery.

[0063] Preferably, in some embodiments, the atomic ratio of O and C satisfies: O:C=1:20-1:12.

[0064] Preferably, in some embodiments, the atomic ratio of O and C satisfies: O:C=1:20-1:15.

[0065] By further optimizing the atomic ratio of O and C within the above range, it is helpful to further improve the capacity and kinetic performance of the negative electrode material and optimize the electrochemical performance of the negative electrode material.

[0066] In some embodiments, the hard carbon has a fibrous corrugated structure. Optionally, the biomass used to prepare the hard carbon has a fibrous structure.

[0067] In the present application, the precursor biomass used to prepare hard carbon can have a fiber structure, and the hard carbon material obtained can have a high content of epoxy groups, and the hard carbon has a fiber wrinkle structure. By making the hard carbon have a fiber wrinkle structure or a fiber structure, it can be used to accelerate ion transmission, shorten the transmission distance, and help improve the kinetic performance; that is, it can shorten the ion transmission path, improve the electrochemical reaction kinetics, effectively reduce the specific surface area of ​​the material, and have sufficient reactive active sites, and at the same time, the material can also have a high gram capacity.

[0068] It should be pointed out that the "fiber structure" described herein has a well-known meaning in the relevant field, and is a morphological structure having fibers (e.g., a substance composed of continuous or discontinuous filaments). It can be understood in a conventional way, and this application does not make any special restrictions on this. On this basis, further, "fiber wrinkle structure" means that the fiber structure has a certain degree of wrinkles, that is, the fiber structure is not linear, but has certain bends or bending segments. In this way, it is beneficial to provide more reactive sites and improve the kinetic properties and capacity of the material.

[0069] Optionally, the above-mentioned biomass includes, but is not limited to, at least one of cellulose, bamboo, coconut shell, macadamia shell, walnut shell, pine nut shell, peanut shell, rice straw, cotton stalk skin, bagasse, reed, reed bamboo, straw, walnut shell, coconut skin or lignin.

[0070] Preferably, the biomass is selected from one or more of cellulose, bamboo fiber, coconut shell, rice straw, cotton stalk skin, and sugarcane bagasse.

[0071] The use of the above-mentioned biomass as precursors to prepare hard carbon is not only widely available, low-cost, and environmentally friendly, but also has a good fiber structure, which can make the prepared hard carbon have better electrochemical properties.

[0072] In some embodiments, the thickness of the carbon coating layer is 5 nm to 10 nm. Further, the thickness of the carbon coating layer is 6 nm to 9 nm. As an example, the thickness of the carbon coating layer can be any one of 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm or a range between any two of them.

[0073] In the present application, the thickness of the carbon coating layer can be adjusted according to the size of the hard carbon in the inner core. The appropriate thickness of the carbon coating layer can not only ensure that the negative electrode material has good processing performance, but also avoid the carbon coating layer being too thick and having too much coating material that affects the timely release of active lithium or affects the electrochemical performance of the battery cell or increases costs. It can also avoid the carbon coating layer being too thin and insufficient to effectively exert the modification effect of the carbon coating layer, that is, it can avoid the thickness being too thin that reduces the effect of the carbon coating layer in improving the primary effect of the material and reducing the specific surface area of ​​the material.

[0074] Optionally, the carbon coating layer comprises pyrolytic carbon formed by thermal decomposition of resin or polymer, wherein the resin or polymer includes, but is not limited to, any one of phenolic resin, urea-formaldehyde resin, epoxy resin, acrylic resin, polyurethane, polyethylene resin, polyaniline, furfural resin, polyethylene glycol, polyethylene oxide, polyacrylonitrile, polyethylene or polypropylene, or any mixture of any proportion of at least two of them.

[0075] In the present application, the core of the negative electrode material can be a hard carbon material derived from cellulose rich in epoxy groups, and the carbon coating layer material can be a small molecule carbon material obtained by pyrolysis and volatilization of a resin such as a phenolic resin or a high molecular polymer.

[0076] [Method for preparing negative electrode material]

[0077] In some embodiments, the present application provides a method for preparing a negative electrode material, which comprises the following steps:

[0078] The pretreated biomass material is soaked in a chloride solution and sintered to obtain a hard carbon precursor;

[0079] The hard carbon precursor is mixed with an acidic solution, and then peroxodisulfate is added, and after mixing, separation and drying, a hard carbon material containing epoxy groups is obtained;

[0080] The hard carbon material containing epoxy groups is subjected to carbon coating treatment to form a carbon coating layer on at least a portion of the surface of the hard carbon to obtain a negative electrode material.

[0081] An embodiment of the present invention provides a method for preparing a negative electrode material, wherein biomass is used as a precursor to prepare hard carbon, and epoxidation treatment is performed during the preparation process to form a hard carbon material rich in oxygen elements, such as a hard carbon material with a high content of epoxy groups that may remain, and then a carbon coating treatment is performed to form a carbon coating layer on the surface of the hard carbon to obtain a negative electrode material. The preparation method has simple process, convenient operation, strong feasibility, green and environmental protection, low cost, and easy to industrialize; the negative electrode material prepared by this method has good structural stability, excellent kinetic performance, and good electrochemical performance.

[0082] It should be understood that all the features and advantages described above for the “negative electrode material” are also applicable to the “negative electrode preparation method” and will not be described in detail here.

[0083] In some specific embodiments, the method for preparing the negative electrode material specifically comprises the following steps (a) to (c):

[0084] Step (a): preparing a hard carbon precursor.

[0085] In some embodiments, in step (a), the pretreated biomass material is soaked in a chloride solution and sintered to obtain a hard carbon precursor.

[0086] In step (a), by soaking the pretreated biomass material in a chloride solution, the chloride solution can be used to shape the material, for example, to facilitate the formation of a hard carbon material with a fiber wrinkle structure. Further, after soaking in the chloride solution, sintering is performed to form a hard carbon precursor through carbonization.

[0087] In some embodiments, in step (a), the biomass material needs to be pretreated to obtain a pretreated biomass material. The preparation of the pretreated biomass material includes: alkali washing, water washing, acid washing, water washing and drying the biomass material in sequence to obtain a pretreated biomass material.

[0088] In this way, by treating the biomass material with alkali washing, water washing, acid washing, water washing, etc., impurities or dirt in the biomass material can be removed, the purity of the prepared hard carbon material can be improved, and the performance of the prepared hard carbon material can be improved.

[0089] Optionally, during the above-mentioned pretreatment, the concentration of the alkaline solution used for alkali washing is 0.5 to 1 mol / L. In the process of pretreating the biomass material, the biomass material is washed with an alkaline solution, and the concentration of the alkaline solution used can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, etc., and of course it can also be other values ​​within the above range, which are not limited here. Optionally, the alkaline solution can be a conventional alkaline solution, such as an alkaline solution such as sodium hydroxide solution (aqueous solution), potassium hydroxide solution (aqueous solution), etc., of course, it is not limited here, as long as it can be used for alkali washing of biomass materials and is not limited to the purpose of this application.

[0090] Optionally, during the above-mentioned pretreatment, the concentration of the acidic solution used for pickling is 0.5 to 1 mol / L. In the process of pretreating the biomass material, the biomass material is cleaned with an acidic solution, and the concentration of the acidic solution used can be 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, etc., and of course it can also be other values ​​within the above range, which are not limited here. Optionally, the acidic solution can be a conventional acidic solution, such as an acid solution (aqueous solution of acid) such as hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, etc., of course, it is not limited here, as long as it can be used for pickling biomass materials and is not limited to the purpose of this application. Preferably, the acidic solution uses hydrochloric acid.

[0091] Optionally, during the above-mentioned pretreatment process, during the alkali washing, acid washing or water washing process, the solid-liquid ratio of the biomass and the solution is 1:50 to 1:200 g / mL. That is, during the alkali washing process, the solid-liquid ratio of the biomass and the alkaline solution is 1:50 to 1:200 g / mL; during the acid washing process, the solid-liquid ratio of the biomass and the acidic solution is 1:50 to 1:200 g / mL; during the water washing process, the solid-liquid ratio of the biomass and water is 1:50 to 1:200 g / mL. As an example, the solid-liquid ratio can be 1:50 g / mL, 1:80 g / mL, 1:100 g / mL, 1:150 g / mL, 1:200 g / mL, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0092] It should be noted that the specific time of the above-mentioned alkali washing, acid washing, water washing and other cleaning steps can be selected and set according to the actual situation of the biomass material. For example, the cleaning time of alkali washing, acid washing, water washing and the like can be 1h to 4h, and can further be about 2h.

[0093] Optionally, during the above pretreatment, the drying temperature is 70°C to 100°C, and the drying time is 10h to 16h. As an example, the drying temperature can be 70°C, 80°C, 90°C, 100°C, etc., and of course it can also be other values ​​within the above range, which is not limited here; the drying time can be 10h, 11h, 12h, 13h, 15h, 16h, etc., and of course it can also be other values ​​within the above range, which is not limited here. Preferably, the drying temperature is 80°C to 90°C, and the drying time is 11h to 13h.

[0094] In some embodiments, in step (a), the biomass material has a fibrous structure.

[0095] In some embodiments, in step (a), the biomass includes, but is not limited to, any one of cellulose, bamboo, coconut shell, macadamia shell, walnut shell, pine nut shell, peanut shell, rice straw, cotton stalk skin, bagasse, reed, reed bamboo, straw, walnut shell, coconut skin or lignin, or a mixture of any proportion of at least two of them.

[0096] Preferably, the biomass material is selected from one or more of cellulose, bamboo fiber, coconut shell, rice straw, cotton stalk skin, and sugarcane bagasse.

[0097] The use of the above-mentioned biomass as precursors to prepare hard carbon is not only widely available, low-cost, and environmentally friendly, but also has a good fiber structure, which can make the prepared hard carbon have better electrochemical properties.

[0098] In some embodiments, in step (a), the biomass material is pretreated, and after obtaining the pretreated biomass material, it is soaked in a chloride solution, wherein the chloride solution includes, but is not limited to, any one of sodium chloride solution, potassium chloride solution or chromium chloride solution, or a combination of at least two of them.

[0099] In the present application, the treated biomass material is immersed in a chloride solution to shape the material.

[0100] Optionally, the concentration of the chloride solution is 0.05-0.5 mol / L; preferably, the concentration of the chloride solution is 0.08-0.3 mol / L; more preferably, the concentration of the chloride solution is 0.1-0.2 mol / L. The concentration of the chloride solution used can be, for example, 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.12 mol / L, 0.15 mol / L, 0.2 mol / L, 0.3 mol / L, 0.5 mol / L, etc.

[0101] Optionally, the solid-liquid ratio of the pretreated biomass material during the soaking process in the chloride solution is 10:1 to 20:1 g / L; that is, the solid-liquid ratio of the pretreated biomass material to the chloride solution is solid (g): liquid (L) = 10:1 to 20:1. As an example, the solid-liquid ratio can be 10:1 g / L, 12:1 g / L, 15:1 g / L, 20:1 g / L, etc.

[0102] In some embodiments, in step (a), the pretreated biomass material is immersed in a chloride solution and then sintered, wherein the sintering is carried out in an inert gas atmosphere, the flow rate of the inert gas is 40-80 mL / min, the heating rate of the sintering is 1-5°C / min, the sintering temperature is 500-1000°C, and the time is 2h-5h. The optional inert gas may be one or more of nitrogen, argon, helium, etc. As an example, the flow rate of the inert gas can be 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, etc.; the sintering heating rate can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc.; the sintering temperature can be 500°C, 550°C, 600°C, 650°C, 700°C, 800°C, 900°C, 1000°C, etc.; the sintering time can be 2h, 3h, 4h, 5h, etc.

[0103] Optionally, in step (a), after sintering, the obtained discharge material can be put into a mortar, ground into powder and sieved to obtain a hard carbon precursor.

[0104] In some embodiments, in step (a), the particle size D50 of the hard carbon precursor prepared is 5 μm to 10 μm. As an example, the particle size D50 of the hard carbon precursor can be any one of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or a range between any two of them.

[0105] As an example, step (a) specifically includes: washing the biomass material with a fibrous structure with alkali for 1h to 3h (such as about 2h), then rinsing the material with water such as deionized water to make the pH of the solution reach 7, and then placing the material in an acidic solution for acid washing for 1h to 3h (such as about 2h), and then rinsing with water (washing) to make the pH of the solution reach 7, and then placing it in an oven for drying, such as, the drying temperature is 80℃ to 90℃, and the drying time is 11h to 13h, to obtain the pretreated biomass material. Then, the pretreated biomass material is placed in a chloride salt solution for soaking for 10h to 30h (such as about 12h), taken out and dried after soaking, and then placed in an inert atmosphere tubular furnace for one calcination (sintering), and after the calcination is completed, the mortar is ground into powder and sieved to obtain a hard carbon precursor with a particle size D50 of 5μm to 10μm.

[0106] Step (b): preparing a hard carbon material.

[0107] In some embodiments, in step (b), the hard carbon precursor prepared in step (a) is mixed with an acidic solution, and then peroxodisulfate is added. After mixing, separation and drying, a hard carbon material containing epoxy groups is obtained.

[0108] In the present application, biomass is used as a precursor to prepare a hard carbon material, and a hard carbon material with a high content of epoxy groups is obtained, and the hard carbon material has a fiber wrinkle structure.

[0109] In step (b), the hard carbon precursor is mixed with an acidic solution, which can be used to expand the interlayer spacing; and then peroxydisulfate is added, which can be used to strengthen the material and perform epoxidation treatment. That is, the material with expanded interlayer spacing is epoxidized by the strong oxidizing effect of peroxydisulfate, thereby forming a carbon material with a high content of epoxy groups.

[0110] In some embodiments, in step (b), the acidic solution includes concentrated sulfuric acid with a mass fraction of not less than 98%. Thus, the concentrated sulfuric acid can play a role in expanding the interlayer distance.

[0111] In some embodiments, in step (b), the peroxodisulfate salt comprises any one of potassium peroxodisulfate, nickel peroxodisulfate or cobalt peroxodisulfate, or a mixture of any proportion of at least two of them.

[0112] In the present application, potassium, nickel and cobalt in the peroxodisulfate salts provided all have catalytic graphitization effects, and the peroxodisulfate salts have strong oxidizing properties. Therefore, by using the above-mentioned peroxodisulfate salts, a strong oxidizing effect can be achieved, and the material with enlarged interlayer spacing can be epoxidized to form a carbon material with a high content of epoxy groups.

[0113] In addition, the catalytic graphitization of metal atoms has also been shown in many studies to have a good catalytic effect on carbon materials, which can effectively reduce the calcination temperature while reducing the number of defects in the material and improving the initial efficiency.

[0114] In some embodiments, in step (b), the ratio of the hard carbon precursor, the acidic solution and the peroxodisulfate is 10:100:1 to 10:500:1 in terms of g:mL:M; that is, the hard carbon precursor (g): 98% concentrated sulfuric acid (mL): peroxodisulfate (M) = 100:10000:1 to 100:5000:2, where M refers to the concentration mol / L. As an example, the carbon precursor (g): 98% concentrated sulfuric acid (mL): peroxodisulfate (M) is 100:10000:1, 100:8000:1, 100:5000:1, 100:5000:2, etc.

[0115] In some embodiments, in step (b), after adding the peroxodisulfate, the mixture is mixed and then separated, such as by filtering, and then placed in an oven for drying, wherein the drying temperature is 70° C. to 100° C. As an example, the drying temperature may be 70° C., 80° C., 90° C., 100° C., etc., and of course, may be other values ​​within the above range, which are not limited here.

[0116] As an example, step (b) specifically includes: mixing the hard carbon precursor obtained in step (a) with an acidic solution such as concentrated sulfuric acid and stirring for 1h to 3h (such as about 2h), then adding peroxydisulfate such as potassium peroxydisulfate, nickel peroxydisulfate or cobalt peroxydisulfate, and stirring for 10h to 30h (such as about 24h). After the stirring, water is continuously added and stirred to separate the solid, and then the obtained material is placed in deionized water, stirred and washed until neutral and filtered, that is, separated. After the separation is completed, it is placed in an oven for drying, for example, the drying temperature is 80°C to 90°C, to obtain a hard carbon material containing oxygen elements, such as epoxy groups.

[0117] Thus, the prepared hard carbon contains oxygen elements, and the implementation of the above-mentioned preparation method can also indirectly prove that the hard carbon contains epoxy groups, so that the hard carbon is an epoxide-rich hard carbon material; the epoxide (epoxy group) in the hard carbon has a large contribution to the effective improvement of the material for the sodium ion adsorption capacity, and at the same time, the epoxide or (epoxy group) in the hard carbon can effectively reduce the free volume of sodium ion migration, that is, compared with the hydroxyl group, the kinetics of the epoxy group is better. In turn, the negative electrode material can show higher capacity and faster kinetics, and the strong attraction of sodium epoxide is used to appropriately expand the interlayer spacing during the sodiumization / de-sodiumization process, which is conducive to the rapid transmission of sodium ions and the improvement of the charge and discharge specific capacity, first effect and cycle performance of the negative electrode material.

[0118] Step (c): performing carbon coating treatment on the hard carbon material.

[0119] In some embodiments, in step (c), the hard carbon material containing epoxy groups obtained in step (b) is subjected to carbon coating treatment to form a carbon coating layer on at least a portion of the surface of the hard carbon to obtain a negative electrode material.

[0120] In the present application, the carbon coating layer includes pyrolytic carbon formed by thermal decomposition of resin or high molecular polymer. That is, the resin or high molecular polymer can be thermally decomposed, which will produce small molecular gas during the thermal decomposition process, which can act as a carbon coating gas source to form a carbon coating layer on at least a portion of the surface of the hard carbon.

[0121] In some embodiments, the resin or polymer includes any one or a combination of at least two of phenolic resin, epoxy resin, acrylic resin, furfural resin, polyethylene glycol, polyethylene oxide, polyethylene or polypropylene. That is, the precursor for forming the carbon coating layer can be selected from resins such as phenolic resin, epoxy resin, acrylic resin, furfural resin, etc.; or the precursor for forming the carbon coating layer can be selected from polymers such as polyethylene glycol, polyethylene oxide, polyethylene or polypropylene, etc.

[0122] Preferably, the resin is selected from phenolic resins.

[0123] In some embodiments, the mass ratio of the resin or polymer to the hard carbon material containing epoxy groups is 5: 1 to 10: 1. As an example, the mass ratio of the resin or polymer to the hard carbon material containing epoxy groups can be 5: 1, 6: 1, 7: 1, 8: 1, 9: 1, 10: 1, etc.

[0124] In some embodiments, the hard carbon material contains C element and O element, and the atomic ratio of O to C satisfies: O:C=1:20-1:10.

[0125] In some embodiments, in step (c), the carbon coating treatment is performed by calcining in an inert gas atmosphere.

[0126] Optionally, the inert gas may be one or more of nitrogen, argon, and helium.

[0127] Optionally, the flow rate of the inert gas is 40 to 80 mL / min. As an example, the flow rate of the inert gas may be 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, etc.

[0128] In some embodiments, in step (c), the heating rate of the carbon coating treatment is 1 to 20°C / min, the temperature of the carbon coating treatment is 500 to 700°C, and the time is 1h to 8h. As an example, the heating rate of the carbon coating treatment can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 10°C / min, 15°C / min, 20°C / min, etc., the temperature of the carbon coating treatment can be 500°C, 550°C, 600°C, 650°C, 700°C, etc., and the time of the carbon coating treatment can be 1h, 2h, 3h, 4h, 5h, 6h, 8h, etc.

[0129] In some embodiments, the thickness of the carbon coating layer is 5 nm to 10 nm.

[0130] As an example, step (c) specifically includes: placing the hard carbon material containing epoxy groups obtained in step (b) and a carbon coating precursor, such as a resin or a high molecular polymer, respectively into two adjacent crucibles (if placed in two crucibles, no impurities will appear and the final product purity will be relatively high), and performing carbon coating treatment, wherein the crucible containing the resin or high molecular polymer is placed at the front end, and then transferring the two crucibles to a tubular furnace, and performing secondary calcination in an inert gas atmosphere, and washing the collected solids with a mass fraction of about 3% dilute HCl (dilute hydrochloric acid) to remove residual metal ions in the material, thereby obtaining a high-performance epoxy group-rich biomass sodium ion battery negative electrode material, that is, obtaining a negative electrode material.

[0131] Thus, based on the above settings, the negative electrode material and preparation method thereof provided by the present invention, the hard carbon material is prepared using biomass material, which can be used as the negative electrode material of the sodium ion battery. From the perspective of green and recyclability, the strategy of synthesizing electrode materials using biomass is of great significance, and the carbon derived from biomass exhibits good electrochemical properties. In addition, since the hard carbon material has a large specific surface area, resulting in a low first effect, in order to effectively suppress the formation of SEI and the corresponding sodium ion consumption, coating technology is often used. In this application, a carbon coating layer is formed on the surface of the hard carbon, and its carbon coating is an efficient means to reduce the specific surface area, which can increase the mechanical strength and conductivity of the active material, and effectively slow down the structural degradation of the material during repeated sodiumization / de-sodiumization. In addition, electrochemical reaction kinetics is also one of the important indicators for investigating the quality of the material. The hard carbon kernel of the present invention, that is, the hard carbon material rich in epoxide, can show higher capacity and faster kinetics, and the strong attraction of sodium epoxide is used to appropriately expand the interlayer distance during the sodiumization / de-sodiumization process, which is conducive to the rapid transmission of sodium ions. In addition, peroxodisulfate was used in the process of preparing the hard carbon core. The catalytic graphitization effect of its metal atoms has been shown in many studies to have a good catalytic effect on carbon materials, which can effectively reduce the calcination temperature while reducing the number of defects in the material and improve the initial efficiency.

[0132] In addition, the sodium ion battery negative electrode material designed by the present invention has a fiber structure, which can shorten the ion transmission path, improve the electrochemical reaction kinetics, effectively reduce the specific surface area of ​​the material, and at the same time has sufficient reaction active sites and high gram capacity. It is a potential high-capacity sodium ion battery negative electrode material.

[0133] [Battery]

[0134] In some embodiments, the present application provides a battery, the battery comprising a negative electrode sheet, the negative electrode sheet comprising the aforementioned negative electrode material, or the negative electrode material prepared by the aforementioned method.

[0135] Since the battery includes the negative electrode material provided in the embodiments of the present application, it can exhibit good electrochemical performance, such as a higher first charge and discharge capacity, excellent first coulombic efficiency and good cycle stability.

[0136] In the present application, the battery may be a sodium ion battery. The battery stacking type may be, for example, a winding type or a laminated type battery, and the structural type may be, for example, a square shell (aluminum shell, steel shell, etc.) battery, a soft pack battery, or a cylindrical battery, etc., without specific limitation. The battery has a high capacity, good cycle effect, and long service life.

[0137] In some embodiments, the negative electrode sheet includes the aforementioned negative electrode material or the negative electrode material prepared according to the aforementioned method. Further, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. In some embodiments, the negative electrode active material layer includes the negative electrode material as described above provided in the present application. Further, the negative electrode active material layer may also optionally include a conductive agent. Further, the negative electrode active material layer may also optionally include a binder.

[0138] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode active material layer is arranged on the two opposite surfaces of the negative electrode current collector. It can be understood that the negative electrode active material layer can also be stacked on any one of the two surfaces of the negative electrode current collector.

[0139] The present application has no particular restrictions on the material of the negative electrode current collector, as long as the purpose of the present application can be achieved, it can be selected according to actual needs. As an example, the negative electrode current collector can be made of metal materials such as aluminum, copper, nickel, stainless steel, nickel-plated steel, or a foil with a surface coating layer made of a related foil material, which has one or more functionalities such as improving the conductivity, improving the adhesion, improving safety, reducing DCR, and increasing the lithium ion conduction ability, for example, it can be a carbon coating layer, carbon coating + graphene / conductive carbon tube / boehmite or alumina and solid electrolyte coating. Of course, in other embodiments, a composite current collector can also be used, and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector can be formed by forming a metal material such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy on a polymer material substrate such as polypropylene, polyethylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, etc.

[0140] The present application embodiment has no particular restrictions on the types of conductive agents and binders in the negative electrode active material layer, as long as the purpose of the present application can be achieved. For example, the binder may include but is not limited to polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene-butadiene rubber), polyvinyl alcohol, polytetrafluoroethylene, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose or sodium hydroxymethyl cellulose. The conductive agent may include but is not limited to at least one of conductive carbon black (Super P), conductive graphite, carbon nanotubes (CNTs), carbon fiber, graphene or conductive polymers. The above-mentioned conductive carbon black includes Ketjen black, acetylene black, etc., and the above-mentioned carbon nanotubes include single-walled carbon nanotubes and / or multi-walled carbon nanotubes.

[0141] The present application has no particular restriction on the mass ratio of the negative electrode material, the conductive agent, and the binder in the negative electrode active material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.

[0142] In some embodiments, the battery further comprises a positive electrode sheet, an electrolyte and a separator. That is, the battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.

[0143] In the embodiments of the present application, in the battery, there is no limitation on the specific materials and structures of the positive electrode sheet, the separator, and the electrolyte, and any components and structures known in the art that can be used for secondary batteries can be selected as long as the purpose of the present application can be achieved.

[0144] Since the battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0145] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents, materials or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0146] Example 1

[0147] The preparation of the negative electrode material comprises the following steps:

[0148] (a) The fibrous biomass material (cellulose) is subjected to alkaline washing for 2 hours, and then the material is rinsed with water such as deionized water to make the pH of the solution reach 7, and then the material is placed in an acidic solution for acid washing for 2 hours, and then rinsed with water to make the pH of the solution reach 7, and then placed in an oven for drying at a drying temperature of 80°C and a drying time of 12 hours to obtain a pretreated biomass material.

[0149] Then, 50g of the pretreated biomass material (cellulose material) was placed in 2.5L of chloride salt solution (0.1mol / L chromium chloride solution) and soaked for 12h. After soaking, it was taken out and dried, and then placed in an inert atmosphere (nitrogen atmosphere) tubular furnace for calcination (sintering). The sintering temperature was 900℃, the time was 2h, and the sintering heating rate was 5℃ / min, that is, the calcination was carried out at a heating rate of 5℃ / min. After the calcination, it was ground into powder in a mortar and sieved to obtain a hard carbon precursor with a particle size D50 of 5-7μm.

[0150] (b) Mix 10 g of the hard carbon precursor obtained in step (a) with 500 mL of concentrated sulfuric acid and stir for 2 h, then add 0.54 g of potassium peroxodisulfate solution (the concentration of potassium peroxodisulfate salt is 0.2 M) and stir for 24 h. After stirring, add water and stir continuously to separate the solid. Then, put the obtained material into deionized water, stir and wash until neutral and filter, that is, separate. After separation, put it into an oven for drying at 80°C to obtain a hard carbon material containing epoxy groups.

[0151] In hard carbon materials, the atomic ratio of O and C satisfies: O:C=1:20.

[0152] (c) Take 2 g of the hard carbon material containing epoxy groups obtained in step (b), and put the hard carbon material containing epoxy groups and phenolic resin into two adjacent crucibles at a mass ratio of 1:5 for carbon coating, wherein the crucible containing phenolic resin is placed at the front end, and then transfer the two crucibles to a tubular furnace for secondary calcination under an inert gas atmosphere, wherein the inert gas is nitrogen, the flow rate of the inert gas is 80 mL / min, the heating rate of the carbon coating treatment is 15°C / min, the temperature of the carbon coating treatment is 500°C, the time is 2 h, the collected solid is washed with about 3% by mass dilute HCl, and cooled to room temperature to obtain a negative electrode material.

[0153] Example 2

[0154] The preparation of the negative electrode material of Example 2 is carried out according to the preparation method of Example 1, except that:

[0155] In step (a), the biomass material is coconut shell material.

[0156] Example 3

[0157] The preparation of the negative electrode material of Example 3 is carried out according to the preparation method of Example 1, except that:

[0158] In step (a), the biomass material is sugarcane bagasse.

[0159] Example 4

[0160] The preparation of the negative electrode material of Example 4 is carried out according to the preparation method of Example 1, except that:

[0161] In step (a), the biomass material is bamboo fiber material.

[0162] Example 5

[0163] The negative electrode material of Example 5 was prepared according to the preparation method of Example 1, except that:

[0164] In step (a), 50g of the pretreated biomass material is placed in 5L of chloride salt solution (0.2mol / L sodium chloride solution) and soaked for 12h. After soaking, it is taken out and dried, and then placed in an inert atmosphere (nitrogen atmosphere) tubular furnace for calcination (sintering). The sintering temperature is 600°C, the time is 5h, and the sintering heating rate is 5°C / min, that is, the calcination is carried out at a heating rate of 5°C / min. After the calcination, it is ground into powder in a mortar and sieved to obtain a hard carbon precursor with a particle size D50 of 5-8μm.

[0165] Example 6

[0166] The negative electrode material of Example 6 was prepared according to the preparation method of Example 1, except that:

[0167] In step (a), 50 g of the pretreated biomass material is placed in 5 L of chloride salt solution (0.3 mol / L potassium chloride solution) and soaked for 12 hours. After soaking, it is taken out and dried, and then placed in an inert atmosphere (nitrogen atmosphere) tubular furnace for calcination (sintering). The sintering temperature is 1000°C, the time is 2 hours, and the sintering heating rate is 3°C / min, that is, the heating rate is 3°C / min for one calcination. After the calcination is completed, it is ground into powder in a mortar and sieved to obtain a hard carbon precursor with a particle size D50 of 6-9 μm.

[0168] Example 7

[0169] The preparation of the negative electrode material of Example 7 is carried out according to the preparation method of Example 1, except that:

[0170] In step (b), 10 g of the hard carbon precursor obtained in step (a) is mixed with 800 mL of concentrated sulfuric acid and stirred for 2 hours, followed by addition of 24 g of potassium peroxodisulfate solution (the concentration of potassium peroxodisulfate salt is 0.2 M), followed by stirring for 24 hours. After the stirring is completed, water is continuously added and stirred to separate the solid. The obtained material is then placed in deionized water, stirred and washed until neutral, and filtered, that is, separated. After the separation is completed, the material is placed in an oven for drying at a temperature of 85°C to obtain a hard carbon material containing epoxy groups.

[0171] In hard carbon materials, the atomic ratio of O and C satisfies: O:C=1:15.

[0172] Example 8

[0173] The negative electrode material of Example 8 was prepared according to the preparation method of Example 1, except that:

[0174] In step (b), 10 g of the hard carbon precursor obtained in step (a) is mixed with 1000 mL of concentrated sulfuric acid and stirred for 2 hours, followed by adding 24 g of potassium peroxodisulfate solution (the concentration of potassium peroxodisulfate salt is 0.1 M) and stirring for another 24 hours. After stirring, water is continuously added and stirred to separate the solid. The obtained material is then placed in deionized water, stirred and washed until neutral and filtered, that is, separated. After separation, it is placed in an oven for drying at a temperature of 90°C to obtain a hard carbon material containing epoxy groups.

[0175] In hard carbon materials, the atomic ratio of O and C satisfies: O:C=1:10.

[0176] Example 9

[0177] The negative electrode material of Example 9 was prepared according to the preparation method of Example 1, except that:

[0178] In step (c), 2 g of the hard carbon material containing epoxy groups obtained in step (b) is taken, and the hard carbon material containing epoxy groups and polyethylene are placed in two adjacent crucibles at a mass ratio of 1:10 for carbon coating, wherein the crucible containing polyethylene is placed at the front end, and then the two crucibles are transferred to a tubular furnace and subjected to secondary calcination in an inert gas atmosphere, wherein the inert gas is nitrogen, the flow rate of the inert gas is 80 mL / min, the heating rate of the carbon coating treatment is 15°C / min, the temperature of the carbon coating treatment is 600°C, and the time is 4 hours. The collected solid is washed with dilute HCl with a mass fraction of about 3%, and cooled to room temperature to obtain a negative electrode material.

[0179] Example 10

[0180] The negative electrode material of Example 10 was prepared according to the preparation method of Example 1, except that:

[0181] In step (c), 2 g of the hard carbon material containing epoxy groups obtained in step (b) is taken, and the hard carbon material containing epoxy groups and acrylic resin are placed in two adjacent crucibles at a mass ratio of 1:8 for carbon coating, wherein the crucible containing acrylic resin is placed at the front end, and then the two crucibles are transferred to a tubular furnace and subjected to secondary calcination in an inert gas atmosphere, wherein the inert gas is nitrogen, the flow rate of the inert gas is 80 mL / min, the heating rate of the carbon coating treatment is 20°C / min, the temperature of the carbon coating treatment is 700°C, the time is 1 h, the collected solid is washed with dilute HCl with a mass fraction of about 3%, and cooled to room temperature to obtain a negative electrode material.

[0182] Comparative Example 1

[0183] The preparation of the negative electrode material comprises the following steps:

[0184] (a) 10 g of cellulose is subjected to alkali washing for 2 h, and then the material is rinsed with water such as deionized water to make the pH of the solution reach 7, and then the material is placed in an acidic solution for acid washing for 2 h, and then rinsed with water to make the pH of the solution reach 7, and then placed in an oven for drying at a drying temperature of 80°C and a drying time of 12 h to obtain a pretreated biomass material.

[0185] (b) placing the pretreated biomass material (cellulose) obtained in step (a) in a crucible and placing it in a tubular furnace, wherein the atmosphere in the tubular furnace is nitrogen and the gas flow rate can be 80 mL / min; the heating rate is 2°C / min, the calcination time is 2 h, and the calcination temperature is 1300°C. After the calcination, a cellulose-derived hard carbon sodium ion battery negative electrode material is obtained.

[0186] The negative electrode material prepared in Comparative Example 1 is a conventional cellulose-derived hard carbon material.

[0187] Comparative Example 2

[0188] The preparation of the negative electrode material comprises the following steps:

[0189] (a) The cellulose material containing a fibrous structure is subjected to alkali washing for 2 hours, and then the material is rinsed with water such as deionized water to make the pH of the solution reach 7, and then the material is placed in an acidic solution for acid washing for 2 hours, and then rinsed with water to make the pH of the solution reach 7, and then placed in an oven for drying at a drying temperature of 80°C and a drying time of 12 hours to obtain a pretreated biomass material.

[0190] (b) placing the pretreated biomass material (cellulose) obtained in step (a) into an inert atmosphere tubular furnace for primary calcination, grinding in a mortar and sieving after the primary calcination to obtain an intermediate material.

[0191] (c) Take 2 g of the intermediate material obtained in step (b), and place the intermediate material and phenolic resin in two adjacent crucibles according to a mass ratio of 1:5, with the crucible containing the phenolic resin placed at the front end. Then transfer the two crucibles to a tubular furnace and carry out secondary calcination in an inert gas atmosphere, wherein the inert gas is nitrogen, the flow rate of the inert gas is 80 mL / min, the heating rate of the secondary calcination is 15°C / min, the calcination temperature is 500°C, the calcination time is 2 h, and the mixture is cooled to room temperature to obtain a negative electrode material.

[0192] The negative electrode material prepared in Comparative Example 2 is a conventional cellulose-derived hard carbon material with a carbon coating layer.

[0193] Comparative Example 3

[0194] The preparation of the negative electrode material comprises the following steps:

[0195] (a) The cellulose material containing a fibrous structure is subjected to alkali washing for 2 hours, and then the material is rinsed with water such as deionized water to make the pH of the solution reach 7, and then the material is placed in an acidic solution for acid washing for 2 hours, and then rinsed with water to make the pH of the solution reach 7, and then placed in an oven for drying at a drying temperature of 80°C and a drying time of 12 hours to obtain a pretreated biomass material.

[0196] (b) placing the pretreated biomass material (cellulose) obtained in step (a) into an inert atmosphere tubular furnace for primary calcination, grinding in a mortar and sieving after the primary calcination to obtain an intermediate material.

[0197] (c) Add 3g of the intermediate material obtained in step (b) and 3g of sodium nitrate to a round-bottom flask, place the flask in an ice bath, add 375ml of 98% concentrated sulfuric acid, stir for 2 hours, add 30g of potassium dichromate and stir for two hours, then stir at room temperature for 48 hours, then add 750ml of 5% sulfuric acid and stir for one hour, and keep the temperature at 98°C during the whole mixing process. After the stirring is completed, water is continuously added and stirred to reduce the temperature of the mixture to room temperature, and then the solid is separated, and the collected solid is alternately washed with 3% dilute H2SO4 and 3% dilute HCl. Then the obtained material is placed in deionized water, stirred and washed until neutral and filtered, and placed in an 80°C oven for drying to obtain a material recorded as a biomass sodium ion negative electrode material, that is, a negative electrode material is obtained.

[0198] The negative electrode material prepared in Comparative Example 3 is an uncoated epoxide carbon material.

[0199] Performance Testing

[0200] 1. Preparation of sodium ion batteries

[0201] (1) The negative electrode materials prepared in the above-mentioned embodiments and comparative examples were used as negative electrode active materials, conductive carbon black (Super P) was used as a conductive agent, and sodium carboxymethyl cellulose (CMC) was used as a binder.

[0202] The negative electrode active material, the binder and the conductive agent are mixed in a mass ratio of 8:1:1 to obtain a mixed material, and the mixed material is fully stirred in deionized water to obtain a corresponding negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and after drying, pressing and other processes, a negative electrode sheet is obtained.

[0203] (2) Provide a metallic sodium sheet as the positive electrode sheet.

[0204] (3) A glass fiber membrane is provided as an isolation membrane.

[0205] (4) Providing an electrolyte, wherein the electrolyte is prepared by dissolving 1.0 mol / L NaPF6 in an organic solvent consisting of diethylene glycol dimethyl ether.

[0206] (5) Assemble the negative electrode sheet, the isolation membrane, and the positive electrode sheet in order and soak them with electrolyte respectively to assemble into NCF2032 button batteries in an argon glove box.

[0207] 2. Test the electrochemical performance of the battery

[0208] The GCD test was performed using a LAND battery test system in a voltage window of 0.01-2V.

[0209] (1) First discharge capacity and first charge capacity test: At a constant temperature of 25°C, discharge at a rate of 0.1C to 0.01V, and record the rate discharge capacity at this time = the first discharge capacity; continue to charge at a rate of 0.1C from 0.01V to 2V, and record the charge capacity at this time as the first charge capacity.

[0210] (2) First coulombic efficiency test: First coulombic efficiency = first charge capacity / first discharge capacity*100%.

[0211] (3) Capacity retention rate (cycle performance and rate performance) test: Under the constant temperature condition of 25°C, discharge at a constant current rate of 1.0C to 0.01V, and continue to charge at a constant current rate of 1.0C to 2V. This is a complete charge and discharge cycle, recorded as cycle 1. Repeat this process until the number of cycles is equal to 200, and then end the test. The charging capacity of the last cycle is the reversible specific capacity, and the charging specific capacity of the last cycle / the charging specific capacity of the first cycle = the capacity retention rate of 200 cycles.

[0212] The test results are shown in Table 1 below.

[0213] Table 1

[0214]

[0215] As can be seen from Table 1, compared with Comparative Examples 1-3, the button-type half-cells prepared using the negative electrode materials provided in Examples 1-10 all have higher initial charge and discharge capacity, higher first inventory efficiency, and good cycle performance and rate performance. It should be understood that the current density used in the present invention when testing the capacity retention rate is 1.0C, that is, a high current density is used for testing, and the capacity retention rate obtained under the high current density is high, which can indicate that the negative electrode material of the present invention has better rate performance, and further indicates that the negative electrode material exhibits good kinetics.

[0216] In addition, through the analysis and comparison of Example 1 and Examples 2-10, it can be seen that the performance of the negative electrode materials prepared by using the biomass materials defined in the present invention, the operating parameters for preparing the hard carbon precursor, the operating parameters for preparing the hard carbon material containing epoxy groups, and the operating parameters for carbon coating treatment defined in the present invention are not much different, and all have obtained high initial charge and discharge capacity, high first inventory efficiency, and good cycle performance and rate performance. Through the analysis and comparison of Example 1 and Comparative Example 1, it can be seen that the conventional cellulose-derived hard carbon material prepared in Comparative Example 1 does not contain oxygen elements and carbon coating layers. Therefore, the first charge and discharge capacity and first inventory efficiency of Comparative Example 1 are low, the capacity retention rate after 200 cycles is low, and the rate performance is poor.

[0217] Through the analysis and comparison of Example 1 and Comparative Example 2, it can be seen that the conventional cellulose-derived hard carbon material with a carbon coating layer prepared in Comparative Example 2 does not contain oxygen elements. Therefore, the first charge and discharge capacity and the first inventory efficiency of Comparative Example 2 are low, the capacity retention rate after 200 cycles is low, and the rate performance is poor.

[0218] Through the analysis and comparison of Example 1 and Comparative Example 3, it can be seen that the uncoated epoxide carbon material prepared in Comparative Example 3 has low initial charge and discharge capacity and initial inventory efficiency, low capacity retention rate after 200 cycles, and poor rate performance.

[0219] in addition, Figure 1 The SEM image of the biomass material provided in Example 1 of the present invention is shown, that is, the morphology of the raw material of the embodiment of the present invention. Figure 1 It can be observed that the biomass material used in the present invention has a fibrous structure. Figure 2 The SEM image of the negative electrode material provided in Example 1 of the present invention is shown. Figure 2 It can be seen that the negative electrode material (hard carbon material) prepared by the present invention maintains the fibrous structure of the precursor. Figure 3 The TEM image of the negative electrode material provided in Example 1 of the present invention is shown. Figure 3 It can be seen that the negative electrode material prepared in the embodiment of the present invention has a good coating effect. Figure 4 The XRD patterns of the negative electrode materials provided by Example 1 (carbon material rich in epoxy groups) and Comparative Example 1 (original carbon material) of the present invention are shown. Figure 4 It can be seen that the 002 characteristic peak of the hard carbon material shifts to a low angle, indicating that the interlayer spacing is enlarged, that is, it indicates that the negative electrode material prepared by the present invention has a larger interlayer spacing. Figure 5 The EDS diagram of the negative electrode material provided in Example 1 of the present invention is shown. Figure 5 It can be proved that the negative electrode material of the present invention is successfully doped with oxygen.

[0220] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0221] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0222] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0223] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0224] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A negative electrode material, characterized in that: The negative electrode material comprises a substrate and a carbon coating layer coated on at least a portion of the surface of the substrate; Wherein, the matrix includes hard carbon, the hard carbon is a biomass-based hard carbon material, and the hard carbon contains C element and O element, and the atomic ratio of O and C satisfies: O:C=1:20~1:

10.

2. The negative electrode material according to claim 1, characterized in that The atomic ratio of O and C satisfies: O:C=1:20~1:

15.

3. The negative electrode material according to claim 1, characterized in that The hard carbon has a fibrous corrugated structure.

4. The negative electrode material according to any one of claims 1 to 3, characterized in that The thickness of the carbon coating layer is 5nm-10nm.

5. A method for preparing a negative electrode material, characterized in that: The following steps are involved: The pretreated biomass material is soaked in a chloride solution and sintered to obtain a hard carbon precursor; The hard carbon precursor is mixed with an acidic solution, and then peroxodisulfate is added, and after mixing, separation and drying, a hard carbon material containing epoxy groups is obtained; The hard carbon material containing epoxy groups is subjected to carbon coating treatment to form a carbon coating layer on at least a portion of the surface of the hard carbon to obtain a negative electrode material.

6. The method for preparing the negative electrode material according to claim 5, characterized in that: The preparation of the pretreated biomass material comprises: The biomass material is sequentially subjected to alkali washing, water washing, acid washing, water washing and drying to obtain a pretreated biomass material; Optionally, the concentration of the alkaline solution used in the alkaline washing is 0.5 to 1 mol / L; Optionally, the concentration of the acid solution used in the pickling is 0.5 to 1 mol / L; Optionally, during the alkali washing, acid washing or water washing process, the solid-liquid ratio of the biomass to the solution is 1:50 to 1:200 g / mL; Optionally, the drying temperature is 70°C to 100°C, and the drying time is 10h to 16h; Optionally, the biomass material has a fibrous structure; Optionally, the biomass material includes at least one of cellulose, bamboo, coconut shell, macadamia shell, walnut shell, pine nut shell, peanut shell, rice straw, cotton stalk skin, bagasse, reed, reed bamboo, straw, walnut shell, coconut skin or lignin.

7. The method for preparing the negative electrode material according to claim 5, characterized in that: The step of obtaining the hard carbon precursor satisfies at least one of the following characteristics (1) to (5): (1) The chloride solution includes at least one of a sodium chloride solution, a potassium chloride solution or a chromium chloride solution; (2) The concentration of the chloride solution is 0.05 to 0.5 mol / L; (3) The solid-liquid ratio of the pretreated biomass material during immersion in the chloride solution is 10:1 to 20:1 g / L; (4) The sintering is carried out in an inert gas atmosphere, and the flow rate of the inert gas is 40 to 80 mL / min; The sintering temperature rise rate is 1-5°C / min, the sintering temperature is 500-1000°C, and the sintering time is 2h-5h; (5) The particle size D50 of the hard carbon precursor is 5 μm to 10 μm.

8. The method for preparing the negative electrode material according to claim 5, characterized in that: The step of obtaining the hard carbon material containing epoxy groups satisfies at least one of the following characteristics (1) to (4): (1) In terms of g:mL:M, the ratio of the hard carbon precursor, the acidic solution and the peroxodisulfate is 100:10000:1 to 100:5000:2; (2) the acidic solution comprises concentrated sulfuric acid having a mass fraction of not less than 98%; (3) the peroxodisulfate salt comprises at least one of potassium peroxodisulfate, nickel peroxodisulfate or cobalt peroxodisulfate; (4) The drying temperature is 70°C to 100°C.

9. The method for preparing the negative electrode material according to any one of claims 5 to 8, characterized in that: The carbon coating layer includes pyrolytic carbon formed by thermal decomposition of resin or high molecular polymer; Optionally, the mass ratio of the resin or high molecular polymer to the hard carbon material containing epoxy groups is 5:1 to 10:1; Optionally, the resin or high molecular polymer includes at least one of phenolic resin, epoxy resin, acrylic resin, furfural resin, polyethylene glycol, polyethylene oxide, polyethylene or polypropylene; Optionally, the carbon coating treatment is a calcination treatment under an inert gas atmosphere; Optionally, the heating rate of the carbon coating treatment is 1 to 20°C / min, the temperature of the carbon coating treatment is 500 to 700°C, and the time is 1h to 8h; Optionally, the carbon coating layer has a thickness of 5 nm to 10 nm.

10. A battery comprising a negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode material according to any one of claims 1 to 4 or the negative electrode material prepared by the method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Method for preparing hard carbon material and lithium ion battery

    CN102723492A

  • Long-cycle hard carbon negative electrode material of lithium ion battery and preparation method of long-cycle hard carbon negative electrode material

    CN114597404A

  • Sodium-ion battery hard carbon negative electrode material and preparation method and application thereof

    CN116253306A

  • Sodium-ion battery core-shell structure bagasse hard carbon-based negative electrode material and preparation method thereof

    CN116332152A

  • Negative pole piece and preparation method thereof, energy storage device and electric equipment

    CN116487528A